CONSTRUCTIVE SOLUTION OF HIGHLY EFFECTIVE PHOTOENERGY MODULE: DEVELOPMENT AND EXPERIMENTAL TESTING - R. V. Zaitsev (National Technical University "Kharkiv Polytechnic Institute", 2019)
Based on experimental study and computer modeling of working temperature influence on the efficiency of Chinese production silicon solar cells identified temperature dependence of efficiency shows the feasibility of using Chinese production Si-SC in the construction of photovoltaic thermal system, which together with the heat pump is part of a combined system for hot water supply, heating and air conditioning. Based on a detailed analysis of the working temperature influence on the efficiency of photovoltaic processes that determine the solar cells work, it has been developed the optimal construction and technological solution of hybrid solar generated module, the main feature of which is the heat exchange block, designed to reduce the solar cells working temperature. The experimental testing of hybrid modules samples equipped with developed cooling system, high-voltage part of power take-off system demonstrates their reliability and high efficiency which allow to achieve the such module efficiency up to 18.5 %.